Moderating Role of Job Autonomy in the Relationship among Antecedents of Organizational Commitment: Empirical Study in Indonesia Social Security Administrator for Health - Abdillah, Willy; Mursalina, Asyraf (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2020)
This study examines the effect of perceived work overload and work-family conflict on organizational commitment with job autonomy as a moderating variable. This study combines Moore (2000a) and Ahuja et al. (2007) IS Turnover model to develop a more parsimony model in explaining the phenomenon of organizational commitment in Social Security Administrator for Health (BPJS Kesehatan). Population of this study is employees of BPJS Kesehatan including Central Office, Deputy for Jakarta-Bogor-Depok-Tangerang-Bekasi (Jabodetabek) Region, Deputy for Central Java and DIY, Deputy for Papua and West Papua, Deputy for North Sulawesi, Central Sulawesi, Gorontalo and North Maluku, and Deputy for Region South Sulawesi, West Sulawesi, Southeast Sulawesi and Maluku. 1650 samples of employee from all level and job positions have gathered by online questionnaire survey. The Result shows that the perception of work overload and work-family conflict affects organizational commitment and is moderated by job autonomy. Implications for future research and stakeholders are further discussed.